Theorizing local migration law and governance - Baumgärtel, Moritz, 1987-; Miellet, Sara (Cambridge University Press, 2022)
In many regions around the world, the governance of migration increasingly involves local authorities and actors. This edited volume introduces theoretical contributions that, departing from the 'local turn' in migration studies, highlight the distinct role that legal processes, debates, and instruments play in driving this development. Drawing on historical and contemporary case studies, it demonstrates how paying closer analytical attention to legal questions reveals the inherent tensions and contradictions of migration governance. By investigating socio-legal phenomena such as sanctuary jurisdictions, it further explores how the law structures ongoing processes of (re)scaling in this domain. Beyond offering conceptual and empirical discussions of local migration governance, this volume also directly confronts the pressing normative questions that follow from the growing involvement of local authorities and actors. This title is also available as Open Access on Cambridge Core.